Self-esteem, body-esteem, emotional intelligence, and social anxiety in a college sample: the moderating role of weight - Abdollahi, Abbas; Abu Talib, Mansor (Routledge, 2016)
To examine the relationships between self-esteem, body-esteem, emotional intelligence, and social anxiety, as well as to examine the moderating role of weight between exogenous variables and social anxiety, 520 university students completed the self-report measures. Structural equation modeling revealed that individuals with low self-esteem, body-esteem, and emotional intelligence were more likely to report social anxiety. The findings indicated that obese and overweight individuals with low body-esteem, emotional intelligence, and self-esteem had higher social anxiety than others. Our results highlight the roles of body-esteem, self-esteem, and emotional intelligence as influencing factors for reducing social anxiety.